Анализ основных тенденций на рынке бронетехники на основе экспонатов выставки Eurosatory 2012 - Волченко, Ю. И.; Ковалив, В. И.; Малахов, В. А. (НТУ "ХПИ", 2012)
У статті проведено аналіз основних розробок сучасних зразків бронетехніки, що були представлені на міжнародній виставці у Парижі Eurosatory 2012. На основі аналізу були окреслені основні напрямки, які мають місце на ринку бронетехніки, а саме ріст зацікавленості в гусеничних броньованих машинах, переміщення пріоритету серед основних характеристик броньованої техніки у бік захищеності екіпажу, поглиблення міжнародної кооперації та спеціалізації.

The article provides an analysis of the main developments in the area of up-to-date armoured vehicles that were exhibited at the Eurosatory’2012 international exhibition held in Paris. Based on this analysis, the main trends in the market of armoured vehicles have been determined, viz. increase of interest in tracked armoured vehicles, shift of priority among the main characteristics of armoured vehicles towards the crew protection, and further development of international cooperation and specialization.
Analysis of the main trends in the market of armoured vehicles in accordance with the results of examination of exhibits at the Eurosatory’2012 exhibition
Keywords: гусеничные бронированные машины; танкостроение; боевые бронированные машины; танки; бронетехника; гусеничный бронетранспортер; системы активной защиты; боевой модуль